Women in literature - Burling, Alexis (Minneapolis, Minnesota : Essential Library, an imprint of Abdo Publishing, 2017)
Introduces important women in literary history, including Maya Angelou, Emily Dickinson, and Roxane Gay.
Includes bibliographical references and index.
Keywords: Women authors -- Biography -- Juvenile literature; Women and literature -- Juvenile literature; Women authors; Women and literature; Women -- Biography; Women authors -- Biography; Women in literature; Women -- Biography